RANCANG BANGUN GAME PENGENALAN HURUF MENGGUNAKAN METODE COLLISION DETECTION - Khasanah, Uswatun; Ardhianto, Eka (Information Technology and Telematics, 2018)
ABSTRACT Lately, the development of gaming technology has grown rapidly in line with the development of information technology. This is marked by the emergence of many game applications on smartphones. Therefore, the writer made a game application for letter recognition using the Collision Detection method. Creation of an Introduction Game This letter can guarantee children's learning resources in recognizing effective letters, because children need learning media that is interesting and educational in the delivery, and also so as not to create a sense of boredom in learning. The method of making this game is Collision Detection starting from the analysis of design, manufacture, testing and maintenance. The game model presented in the form of letters and baskets, and there are 3 levels, where each level has a different time and has a different speed. Tests carried out include, testing of android devices. The results showed that the game "Introduction to Letters" made using construct 2 can be run on mobile devices with Android platforms easily by the users.